Reactivity and interaction of glutathione of erythrocytes and oxygen blood transport function in haemic hypoxia of hemolytic genesis - Lanovenko, I.I.; Gaschuk, A.P. (Reports of the National Academy of Sciences of Ukraine, 2022)
Glutathione (GSH) is an universal regulator of biochemical, physiological and oxygen homeostasis in humans and animals. The state of the erythrocyte glutathione system significantly affects hemoglobin activity and the mechanisms of regulation of the oxygen blood transport function (OBTF) of the blood in general. The studies of the functional significance and role of GSH in the genesis of hypoxic conditions and, particularly, hemic hypoxia in anemia are relevant given the polyprotective properties of GSH. The purpose of the work is to investigate changes and the interaction of erythrocyte glutathione and the the oxygen blood transport function during hemic hypoxia of hemolytic genesis. In a laboratory rats experiment, a model of hemic hypoxia (HH) of hemolytic (use of phenylhydrazine) genesis was reproduced. Under the conditions of HH, effects on the metabolism of GSH were used: stimulation of the formation of cysteamine (CA) synergist and GSH donor glutargin using GSH synergist; inhibition of a GSH diethylmaleate antagonist. Arterial and mixed venous blood was used for analysis. The definitions of the investigated parameters were carried out in the initial state and after exercising of experimental effects. The following indices were determined: hemogram indicators, bone marrow cell composition and iron metabolism parameters; the quantity of reduced (GSH) and oxidized (GSSG) glutathione and the activity of the GSH enzyme glutathione reductase (GR) in blood red blood cells; indicators of oxygen blood transport function (OBTF) — parameters for hemic hypoxia. In experiments on rats with modeling haemic hypoxia of hemolytic genesis, the damage of OBTF (delivery and use O2 decrease, metabolic acidosis) and a significant decrease in the content (by 2,85 times) of the glutathione (GSH) and activity (by 4,89 tim es) of the GR in erythrocytes of blood are determined. Inhibition of the generation of GSH (by means of diethylmaleate) increases the GSH deficiency and OBTF damages; and the activation of the generation of GSH (by means of cysteamine and glutarine) increases production GSH, it strengthens activity GR and restores OBTF. The high sensitivity and efficiency of regulation of the oxygen blood transport function under anemia has been established using targeted effects on glutathione metabolism. The possibility of haemic hypoxia correctoin by means of the use of glutathione and its donors is grounded.